The lived experience of high school instructors teaching concurrent enrollment courses - Exby, Heather Dickinson, author; Davies, Timothy Gray, advisor; Carlson, Laurie, committee member; Hall, Bruce, committee member; Hegeman, Diane, committee member (Colorado State University. Libraries, 2014)
This qualitative phenomenological study explored the lived experiences of high school instructors teaching concurrent enrollment courses. The phenomenon was examined using the Stevick-Colaizzi-Keen approach for phenomenological research as outlined by Moustakas through data collected in personal interviews with 10 high school instructors who taught concurrent enrollment college courses in their high schools. Instructional Quality, Passion, Commitment to Students, and Pride emerged as the four structural themes that framed the meaning of the phenomenon. Balance within a Liminal Space emerged as the essence of the phenomenon. Approved high school instructors approached their college concurrent enrollment responsibilities with honor and pride in teaching at the college level, as well as with duty to provide rigorous academic instruction that supported student development and transition and met the college instructional expectations. The phenomenon of teaching of college courses in a high school environment required teachers to balance the demands of their high school environment and instructional philosophies of secondary education with the curricular demands and differing instructional philosophies of higher education. This resulted in concurrent enrollment's unique instructional position in a liminal or threshold space between secondary and postsecondary education sectors. The liminal space of concurrent enrollment, although laden with ambiguity and tension, provided teachers with unique opportunities to facilitate the teaching of college academic curriculum integrated with time-built relationships with students and commitment to student learning to create positive, enhanced academic experiences for students. The "productive tension" of the liminal space can serve as a unique and optimal laboratory for addressing some of the pervasive problems with successful matriculation to college and strengthen the college transition process for greater student success.
Keywords: college transition; concurrent enrollment; dual enrollment; matriculation; secondary education; teaching and learning